Analysis of new approaches to language teaching in the light of using advanced multimedia media (CELL + CALL) [In Persian] - Mehran Memari (International E-Research Foundation (Bonyan Pouya Pajooh Andisheh Institute), 2021)
Computer communication has played an important role in the present age in the field of teaching language concepts. This type of communication, or in other words, "CALL", which stands for computer-assisted language learning, is served by new technologies such as laptops, tablets, smartphones, audio playback platforms such as mp3s, interactive whiteboards, etc. . But a useful method, especially for newcomers, is to divide the use of the computer according to the practical roles of the teacher and the tool. Where the computer has some kind of educational function, a program regularly displays words or a set of online grammar exercises that can be used by the teacher. Other language learning activities include social media, an email program, or a web search engine such as Google, which in turn represents the use of a tool in which the computer has no obvious educational function. Topics that are not covered here include digital resources such as text, audio, video, and other multimedia media that are readily available on the web or through proprietary applications. They provide language content for learners to support a person's reading and listening skills and to act as a gateway to receiving target language cultures. They are also able to provide content to support interactive two-way discussions. This study tries to discuss the new opportunities and advances provided by computers in language teaching. This study also tries to analyze the dimensions of modern computer communication as a facilitator of language learning. New computer communications are making a significant contribution to language learning in the present age.